Peak airway pressure during high frequency jet ventilation: theory and measurement. - Young, J; Dorrington, K (1989)
A mathematical model has been developed to predict the peak airway pressure attainable during jet ventilation. The theory assumes inviscid and incompressible flow and agrees closely with experimental results using bench models of simple jet systems and systems using a tracheal tube designed for jet ventilation. The results of a previous published study also show good agreement with the predicted results.